The Hispanic-Catholic Meridian of Argentina in the 1930s (Palimpsesto, 2020)
The following paper describes the Argentine intellectual field between 1930 and 1945 from the notion of network (Maíz, 2011), a concept that envisages dialogical exchanges of a certain era through the press, epistolary and paratexts. Through the networks of journalistic communication, we will exhibit the controversies unleashed between the pages of Sur and Criterio. Our goal is to demonstrate how the first magazine has literary legitimacy, while the second one is evidence of nationalist hegemony that crystallizes in Peronism from 1943. In short, we offer an x-ray of the debates around the identity, culture and nationalism in the Argentine press between 1930 and 1945.
Keywords: Networks; meridiano; intellectual field; nation; the mith of the catholic nation